2018
DOI: 10.1038/bjc.2017.479
|View full text |Cite
|
Sign up to set email alerts
|

KRAS mutations in cell-free DNA from preoperative and postoperative sera as a pancreatic cancer marker: a retrospective study

Abstract: Changes in KRAS mutation status between preoperative and postoperative cfDNA may be a useful predictive biomarker for survival and treatment response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
73
2
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 77 publications
(78 citation statements)
references
References 24 publications
(37 reference statements)
1
73
2
2
Order By: Relevance
“…Recently, blood‐based tests, also known as liquid biopsy, serve as potential alternative measures to radiological tests and tissue biopsies. In particular, ctDNA reflects disease status and holds advantages for the diagnosis, prognosis and monitoring of several cancers . Recently, targeted analyses of specific cancer‐associated genes in plasma cfDNA obtained satisfactory clinical applicability for several cancers .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, blood‐based tests, also known as liquid biopsy, serve as potential alternative measures to radiological tests and tissue biopsies. In particular, ctDNA reflects disease status and holds advantages for the diagnosis, prognosis and monitoring of several cancers . Recently, targeted analyses of specific cancer‐associated genes in plasma cfDNA obtained satisfactory clinical applicability for several cancers .…”
Section: Discussionmentioning
confidence: 99%
“…In particular, ctDNA reflects disease status and holds advantages for the diagnosis, prognosis and monitoring of several cancers. 16,[33][34][35] Recently, targeted analyses of specific cancer-associated genes in plasma cfDNA obtained satisfactory clinical applicability for several cancers. 36 cfDNA analysis can include not only somatic mutations but also fragment size, a metric that has received comparatively scant attention.…”
Section: Discussionmentioning
confidence: 99%
“…Based on these similar mutation types, it was suggested that the mutation of TP53 in this cohort might be a potential biomarker for predicting prognosis in Chinese patients with CCA. KRAS, the main subtype of the RAS gene family, has been reported to promote a variety of lethal human tumors, such as lung, colon and pancreatic cancer (36,37). Several studies have reported KRAS as a tumor biomarker (37)(38)(39) and that the co-mutation of TP53 and KRAS in many tumors (30,40).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, subtype analysis revealed that patients with Kras G12D mutation had an extremely poor prognosis with a median OS of 15.3 months in resectable pancreatic cancer, while other studies showed different results . Change of Kras mutation in ctDNA could also be used to monitor treatment response in metastatic pancreatic cancer and Kras mutation detected in ctDNA after surgery is associated with early recurrence and metastasis . Two patterns (G12V and G12D) of Kras mutation account for about 90% of all mutations in pancreatic cancer and both mutation rates range from 30% to 50%.…”
Section: Discussionmentioning
confidence: 99%
“…22,23 Change of Kras mutation in ctDNA could also be used to monitor treatment response in metastatic pancreatic cancer and Kras mutation detected in ctDNA after surgery is associated with early recurrence and metastasis. 8,24 Two patterns (G12V and G12D) of Kras mutation account for about 90% of all mutations in pancreatic cancer and both mutation rates range from 30% to 50%. Therefore, in this study, we detected these two mutation sites in ctDNA of advanced pancreatic cancer, and found that both Kras G12D mutation and Kras G12V mutation were associated with poor prognosis, which was consistent with other studies.…”
Section: Discussionmentioning
confidence: 99%